Global Shift / The Internationalization of Economic Activity: Second Edition - Dicken Peter (Paul Chapman Publishing, 1992)
Economic activities are becoming increasingly globalized - functionally integrated across national boundaries in ways which are dramatically altering the fortunes of countries and localities in the world economy. Acknowledgements, Introduction, Patterns of Global Shift, The Changing Global Map: Trends in Production and Trade, Processes of Global Shift, The Role of Technological Change, Global Organization and Reorganization of Economic Activity: Networks of Relationships, Global Shift: The Picture in Different Sectors, ''Wheels of Change'': The Automobile Industry, ''Chips and Screens'': The Electronics Industries, Stresses and Strains of Adjustment to Global Shift, Making a Living in the Global Economy: Problems of Adjusting to Global Shift, Epilogue: ''Through a Glass, Darkly'', Bibliography, Index.